Antioxidant protection in cryopreservation: the role of Trolox in preserving human cord blood nucleated cells - Zubov, Pavlo; Zubova, Oksana (Problems of Cryobiology and Cryomedicine, 2025)
The paper presents experimental data on determining quantitative and qualitative characteristics of human cord blood (CB) nucleated cells (NCs), including hematopoietic progenitor cells (HPCs), after cryopreservation in solutions with different concentrations of DMSO and antioxidant Trolox and in vitro transfusion simulation. Our findings showed that the incubation of frozen-thawed cord blood NCs for an hour under in vitro physiological conditions caused a decrease in their survival and viability compared to the data obtained immediately after thawing. These changes are likely due to the destruction of some cells, contained high level of reactive oxygen species (ROS) because of mechanical and metabolic injuries caused by freeze-thawing factors. The supplement of antioxidant Trolox at concentrations of 50 or 70 μM to the cryoprotective DMSO-containing medium at equilibration stage promotes the reduction of cells with excessive ROS content and increases their survival and viability both after thawing the cell suspension and after transferring to in vitro physiological conditions. The results obtained for determining the delayed cell survival demonstrate the efficiency of using antioxidant Trolox and the prospects for developing Trolox-containing cryoprotective mixtures for freezing cord blood NCs, including HPCs, and may become a prerequisite for improving the existing approaches and developing the new ones to their cryopreservation and long-term storage in low-temperature banks. Probl Cryobiol Cryomed. 2025; 35(2): 92–102